Gestating sows exhibit greater ileal amino acid digestibility of corn distillers grains, rapeseed meal, and cottonseed meal than growing pigs, but not soybean meal - B. Lei; G. Lv; X. Mo; L. Hua; X. Jiang; B. Feng; L. Che; S. Xu; Y. Lin; F. Wu; D. Wu; Y. Zhuo (Animal, 2025)
Precise measurement of ileal amino acid digestibility in feed ingredients is vital for optimising sows’ nutrient requirements and feed utilisation. We hypothesised that the ileal amino acid digestibility of feed ingredients for swine, which usually are determined in growing pigs, may not accurately reflect their actual digestibility in gestating sows. This experiment aimed to compare the apparent and standardised ileal CP and amino acid (AA) digestibility of four protein-feed ingredients, including soybean meal, corn distiller’ dried grains with solubles (DDGS), rapeseed meal (RSM), and cottonseed meal (CSM), between gestating sows and growing pigs. These feed ingredients were used as the sole sources of CP and AA to formulate four experimental diets for both gestating sows and growing pigs. Two nitrogen-free diets were formulated to estimate the endogenous AA losses for gestating sows and growing pigs, respectively. Ten barrows, with an average weight of 35.0 ± 1.6 kg, were randomly assigned to five treatments in a replicated 5 × 4 incomplete Latin square design (five diets and four periods) with eight replicates. For the sow trial, ten gestating sows, with an average weight of 238.9 ± 9.3 kg, were randomly assigned to five diets in a replicated 5 × 3 incomplete Latin square design (five diets and three periods) with six replicates. Each diet was fed for 7 days: 5 days for adaptation, with ileal digesta collected after the first meal on days six and seven. There were no differences between growing pigs and gestating sows for the standardised ileal digestibility (SID) of CP and AA from soybean meal. However, gestating sows had greater SID for isoleucine, leucine, phenylalanine, valine, alanine, cysteine, and glutamic acid from DDGS compared with growing pigs (P < 0.05). In addition, gestating sows had greater SID for CP and AA from RSM, except for lysine, tryptophan, cysteine, and glycine, compared with growing pigs. Gestating sows also had greater SID of leucine (P = 0.02) when fed the CSM diet compared with growing pigs. The reduced SID of CP and AA in growing pigs fed the DDGS, RSM, and CSM diet was associated with decreased activities of trypsin and chymotrypsin in the ileal digesta. In conclusion, gestating sows had greater ileal AA digestibility for non-conventional feed ingredients such as DDGS, RSM, and CSM, which stresses the importance of a separate feed ingredient value for sows.